Pengelolaan Limbah Medis Covid-19 Berdasarkan Undang-Undang 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup - Nia Ramadhanty Purwanto; Syauqi Al Amin; Ainun Mardiyah; Yosia Retno Wahyuningtyas (Fakultas Hukum Universitas Surabaya, 2020)
Indonesia is currently undergoing major changes caused by Covid-19. One of the big changes is the increase in medical waste. Article 1 number 1 of Government Regulation No. 101 of 2014 concerning Waste Management of Hazardous and Toxic Materials (